Navigating Social Skills in Elementary School: Children's Peer Interactions in the Digital Age - Budiansyah Budiansyah; Ilham Arya Susanto; Elita Aidillah (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Digital technology is increasingly reshaping children's socialization, and peer relationships now extend across both physical and virtual spaces. While previous studies have examined online behavior and digital literacy, there is a limited understanding of how elementary school children develop and negotiate social skills in these hybrid environments. Grounded in post-positivist philosophy, this qualitative case study investigates how children navigate digitally mediated peer interactions in two elementary schools in Palembang, Indonesia. The study involved 42 students, 12 teachers, and 15 parents. Collected data through semi-structured interviews, participant observations, and digital artifact analysis, and examined using thematic analysis. The findings reveal the emergence of digital empathy as a hybrid competence integrating emotional responses across online and offline settings. Digitally active students exhibited stronger collaborative problem-solving but tended to marginalize less active peers, while teachers' guidance in digital social interactions remained inconsistent. The study recommends integrating digital citizenship with social-emotional learning and strengthening teacher professional development. Future research should adopt longitudinal and cross-socioeconomic approaches to examine the evolution of digital social competencies and their impact on learning practices.